KONSEP DAN URGENSI PENDIDIKAN BAHASA ARAB MENURUT IBNU KHALDUN DALAM KITAB MUQADDIMAH DAN RELEVANSINYA DI INDONESIA - Rasyid, Hilman (Departemen Pendidikan Bahasa Arab, 2018)
This research is motivated by the lack of attention to the study of Arabic and reading the Koran. Considering its importance, the need for studies related to the concept and importance of education in Arabic. Therefore, Ibn Khaldun thought of as a great thinker in Islamic education became the main object of this study. The purpose of this study was to demonstrate the concept and importance of education in Arabic according to Ibn Khaldun who then thought relevanced in Indonesia. To achieve these objectives, the researcher uses descriptive research method with qualitative approach. Based on the research results, Ibn Khaldun confirms that the Arabic language education is very important to learn. In fact he believes that education is more important than the education of the Koran and other religious sciences. Ibn Khaldun's thoughts are still relevant in education in Indonesia, especially in Madrasah Aliyah PPI 67 Benda